Physico-Chemical and Microbial Analysis of the Effects of Abattoirs Operation in Estako-West and Central, Edo-State, Nigeria (Global Journal of Science Frontier Research, 2016)
Abattoir wastewater has a complex composition and very harmful to the environment. There is always need for reduction in the impact of natural and most especially anthropogenic pollution to enhance water quality, food safety and sustainable development. Physico-chemical and microbial properties analysed using standard laboratory procedures were temperature, pH, conductivity, turbidity, total solid (TS), total dissolved solid (TDS), total suspended solid (TSS), dissolved oxygen (DO), acidity, alkalinity, total hardness, calcium and magnesium hardness, chloride, iron and nitrate. Temperature ranged from 28.04-29.12C, pH between was 7.67-8.01, Alkalinity is 0.45 mg/l, TS, BOD and TSS were 700 mm/l, 48 mm/l, 500 mm/l, DO is 2,100 ppm. Holistic outputs of the investigation revealed various water samples were contaminated with E. Coli and other enteric bacteria. The presence of coliform staphylococcus aures indicated the presence of microorganisms which are associated with water borne disease.
Keywords: slaughterhouse; wastewater; environment; bacteria; abattoirs; water quality; physico-chemical and microbial properties; hazard and safety